SOME PECULIARITIES OF TRIBOMECHANICS ELEMENTS USE IN DESIGN AND OPERATION OF DRILLING MACHINES FOR DRILLING OF UPRISING WORKINGS AND WELLS - Malinovskyi, Yurii; Tsvirkun, Sergij; Sytnyk, Serhii; Vlasenkov, Dmyro; Rybak, Dmitro; Oliinyk, Svitlana (Problems of Friction and Wear, 2024)
Modern mining enterprises widely use rotary drilling rigs equipped with ball drill heads, which are used to drill holes ∅250 - ∅320 mm in hard rocks for blasting operations. Drilling of such wells is associated with the use of significant axial forces and torques , which cause longitudinal deformation (compression) and torsional deformation of the rods and the drillstock as a whole. Therefore, the intensification of rotary drilling processes to increase the diameter of the drilled well is associated with significant technical difficulties and economic costs. In a number of practical cases, it is possible to drill large diameter wells in two stages. The first stage involves drilling a small-diameter (∅250 - ∅320 mm) advance well from the outer horizons of a mining enterprise (e.g., a mine) to a lower horizon or a network of horizontal workings connected to a pit. After drilling the advance borehole (∅250 - ∅320 mm), a drill bit is lowered to the horizon below, which is put on a drill bit instead of a small diameter crown. After replacing the working tool with a diameter of ∅250 - ∅320 mm with a drill bit with a diameter of ∅1500 - ∅3000 mm, drilling is carried out vertically upwards (sometimes at an angle). When drilling, the drill stand is subjected to torque and tensile axial force. In this mode of operation, the loads on the drillstring increase significantly, but the longitudinal axis of the drillstring remains straight, as the influence of longitudinal bending is eliminated, and the influence of drillstring unbalance due to initial misalignment and centrifugal forces is reduced. However, the moment of friction forces during drilling increases significantly, the influence of the drillstring stiffness increases, and there is a possibility of longer stops during the driller’s operation in the bottom hole, while the value of the elastic forces of the drillstring decreases with an increase in its length, and therefore the twist angle increases. In the case of an increase in the angle of rotation of the drill string, the dynamic torque and tangential stresses increase due to significant differences in the angular speed of rotation of the string (from to 0). In this case, there are significant changes in the kinetic energy of the pile with a decrease in the angular velocity of its rotation. In fact, a decrease in the rigidity of the mill leads to an increase in the increase in the kinetic energy of the system on the drill. That is, the dynamic angle of shaft torsion increases and leads to the manifestation of a torsional impact with a large coefficient of dynamism ( ). As follows from the industrial tests of the 2KV 3000 machine, the possibility of a torsional impact in the driller-drillstock-rotator system under the influence of a variable torque of friction forces between the rock and the tool was not taken into account. Therefore, at the maximum length of the drillstring, the increase in the kinetic energy of the impact causes the largest dynamic angle of twisting of the drillstring, which is perceived by the first rods from the driller, and they experience the ultimate induced normal stresses that lead to rod breakage. For these reasons, for the efficient operation of drilling rigs in the drilling mode, it is necessary to create and apply an engineering methodology for calculating the dynamic parameters of the drill string and the rig as a whole under the influence of the frictional interaction between the tool and the rock.